The effect of assets structure, sales growth, liquidity, and assets growth on capital structure (debt to equity ratio) in pt. Kereta api indonesia (persero) period 2016 – 2021 - Neneng Susanti; Vicka Rachmawati; Hasan Harfudin (International Journal of Artificial Intelligence Research, 2022)
The efforts to determine the capital structure need to consider and pay attention to the various variables that influence it; since directly the capital structure decision will affect the condition and value of the company and determine the company's ability to continue to flourish. This study purposes to observe on how much influence the asset structure, sales growth, liquidity, and asset growth have on the capital structure of PT. Kereta Api during 2016-2021 periods. The method used in this research is descriptive and verification method with a quantitative approach. The technique taken is a saturated sampling technique. The data analysis technique used is multiple linear regression analysis. By using e-views12 the results in this study indicate that partially asset structure has no significant effect on capital structure, sales growth has a significant effect on capital structure, liquidity does not have a significant effect on capital structure, and asset growth has a significant effect on capital structure, as well as simultaneously asset structure, sales growth, liquidity and asset growth have a significant effect on the capital structure